2018
DOI: 10.1111/jav.01728
|View full text |Cite
|
Sign up to set email alerts
|

Preen oil chemical composition encodes individuality, seasonal variation and kinship in black kites Milvus migrans

Abstract: Evidence that bird odour can encode social information that can be used in chemical communication is growing, but is restricted to a few taxonomic groups. Among birds, diurnal raptors (i.e. birds from the Accipitriformes and Falconiformes order) have always been considered as mainly relying on their visual abilities. Although they seem to have a functional sense of smell, whether their odour can convey social information has yet to be determined. Combining gas‐chromatography‐mass‐spectrometry (GCMS) and micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 80 publications
1
13
0
Order By: Relevance
“…Our results add further support to the existence of age‐related differences in the composition of uropygial gland secretions, as reported in species such as domestic chickens (Sandilands et al 2004a), starlings Sturnus unicolor (Amo et al 2012) and gray catbirds Dumetella carolinensis (Shaw et al 2011), but not in others such as black kites Milvus migrans (Potier et al 2018). We found that secretions of adults had more compounds than juveniles, with significantly higher relative proportions of alcohols, but lower proportions of pyrazines, steroids and ketones.…”
Section: Discussionsupporting
confidence: 88%
“…Our results add further support to the existence of age‐related differences in the composition of uropygial gland secretions, as reported in species such as domestic chickens (Sandilands et al 2004a), starlings Sturnus unicolor (Amo et al 2012) and gray catbirds Dumetella carolinensis (Shaw et al 2011), but not in others such as black kites Milvus migrans (Potier et al 2018). We found that secretions of adults had more compounds than juveniles, with significantly higher relative proportions of alcohols, but lower proportions of pyrazines, steroids and ketones.…”
Section: Discussionsupporting
confidence: 88%
“…To our knowledge, no studies have tested whether natural seasonal dietary changes affect preen oil composition, but laboratory studies have shown that diet affects preen oil composition in captive birds (Apandi & Edwards, 1964; Thomas et al ., 2010, p. 201; Kanakri et al ., 2016). However, captive birds fed a constant diet still exhibit seasonal changes in preen oil (Reneerkens et al ., 2007b; Whelan et al ., 2010; Tuttle et al ., 2014; Potier et al ., 2018; Grieves et al ., 2020), demonstrating that differences in diet can only partly explain seasonal changes in preen oil composition. Sex differences in the chemical composition of preen oil may be driven partly by sex differences in diet, which is common in species with size dimorphism [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In darkeyed-juncos, for example, it was found that males with a relatively more 'male-like' odour profile sired more offspring in their own nest, which had a higher survival rate (Whittaker et al 2013). Preen gland secretions may also provide information on MHC similarity or diversity (Leclaire et al 2014(Leclaire et al , 2017Slade et al 2016;Grieves et al 2019a, b) and relatedness (Krause et al 2012;Leclaire et al 2012;Potier et al 2018), which both may also influence mate choice. This would require aspects of the chemical composition to be repeatable within individuals over time, thereby allowing Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical composition of the preen gland secretion has been found to hold information on sex in several species (Jacob et al 1979;Reneerkens et al 2007;Martín-Vivaldi et al 2009;Whittaker et al 2010;Zhang et al 2010;Leclaire et al 2011;Amo et al 2012a;Mihailova et al 2014;Tuttle et al 2014;Grieves et al 2019b), but not in some others (Reneerkens et al 2007;Gabirot et al 2018). In addition, it has been found that the secretion may hold information on age (Shaw et al 2011), the major histocompatibility complex (Leclaire et al 2014(Leclaire et al , 2017Slade et al 2016;Grieves et al 2019b), genetic relatedness (Leclaire et al 2012;Potier et al 2018), individual identity (Whittaker et al 2010) and health status (Grieves et al 2018;Díez-Fernández et al 2020). Moreover, behavioural studies have shown that olfactory cues are used in kin recognition (Bonadonna and Sanz-Aguilar 2012;Krause et al 2012;Caspers et al 2015Caspers et al , 2017 and influence mate choice (Balthazart and Taziaux, 2009;Caspers et al 2015;Grieves et al 2019a, b).…”
Section: Introductionmentioning
confidence: 99%